The Long-Term Outcomes of Microvascular Decompression for Trigeminal Neuralgia Compared with Percutaneous Techniques. (16th November 2020) - Noorani, Imran; Lodge, Amanda; Vajramani, Girish; Sparrow, Owen
Abstract: INTRODUCTION: Surgical treatment of trigeminal neuralgia (TN) includes microvascular decompression (MVD) and percutaneous techniques. Direct comparisons of these techniques, including long-term outcomes and complications, are lacking. METHODS: This is a large retrospective analysis of prospectively collected data from a single centre. We analysed results from 217 consecutive patients undergoing 229 MVD procedures, and 210 patients undergoing 393 percutaneous procedures (152 GR, 155 TC, 87 BC) for TN. Patient records and telephone follow-up were used to determine demographic and operative details and surgical outcomes. Follow up ranged from 12 months to 20 years. All were performed by 1 of 2 neurosurgeons. RESULTS: MVD patients were significantly younger than those undergoing a percutaneous procedure (58.6 vs 71.0 years respectively, p < 0.001). 80.3% of patients had BNI class I or II pain scores after an MVD, compared with 53.7% for GR, 64.3% for TC and 61.6% for BC. The overall complication rate for MVD was 29.8%, or 13.0% excluding the transient ones (diplopia, ataxia, hearing loss and tinnitus). Complication rates for percutaneous procedures were 30.3, 27.1, and 43.5% for GR, TC and BC respectively. MVD had a low risk of serious complications including stroke, intracranial bleed and CSF leak; these did not occur with percutaneous procedures, although these led to major dysaesthesiae or anaesthesia dolorosa in 1.5%. Kaplan-Meier analysis revealed the long-term durability of pain relief was significantly better with MVD than GR, TC or BC (p < 0.001; 25% pain recurrence at 84, 3, 7 and 20 months respectively). CONCLUSION: MVD provides the best pain relief and durability compared with percutaneous procedures in those medically fit to have an open operation. The spectrum of complications differ between these procedures, with MVD having a small risk of stroke and CSF leak.